THE EFFECTS OF INTERPERSONAL COMMUNICATION SKILL AND VOCABULARY MASTERY TOWARDS STUDENT’S SPEAKING SKILL - suhendar suhendar (Journal of English Language and Literature (JELL), 2016)
The objective of this research is to find out (1) The effects of interpersonal communication skill and vocabulary mastery jointly toward student’s speaking skill at private universities in East Jakarta; (2) The effect of interpersonal communication skill towards student’s speaking skill at private university in East Jakarta; (3) The effect of vocabulary mastery towards student’s speaking skill at private university in East Jakarta. In connection to which, research methodology used by the researcher is explanatory survey with quantitative approach through correlation method. The researcher concluded that population is collected from a number of groups interest to the researcher, a number of group which researcher would like to make the results of the study to be reported. As for the sample of which is undertaken by random sampling and the samples thereof are 40 people. Finally, the research findings are: (1) There are significant effects of interpersonal communication skill and vocabulary mastery jointly towards student’s speaking skill at private university in East Jakarta. It is proved by Faccount= 25.835 > F table (0,05,2,37) = 3,252, and sig = 0.000 < 0.05. 2) (2) There is significant effect of student’s interpersonal communication skill towards student’s speaking skill at private university in East Jakarta. It is proved by taccount= 4.436 > ttable 2.024, and sig = 0.000 < 0.05. (3) There is significant effect of vocabulary mastery towards student’s speaking skill at private university in East Jakarta. It is proved by taccount= 3.250>ttable 2.024, and sig = 0.002 < 0.05